Ecophysiological aspects limiting natural regeneration - Turchetto, Felipe; Tabaldi, Luciane Almeri; Rorato, Daniele Guarienti; Gomes, Daniele Rodrigues (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
Natural regeneration comprises the initial stages of establishment and development, and is considered a slow and unpredictable process, due to the complex interaction between the successful establishment of seedlings and different environmental factors. Thus, the aim of this study was show a review addressing eco-physiological factors influencing the natural regeneration of forests as reserves of seed, production and seed dispersal, germination and dormancy, temperature, and water availability and light. Knowledge of the effect of these factors and their interactions with the community are essential to forest management, regarding its management and revegetation of disturbed areas. Thus, simulations of regeneration constitute naturally a very useful tool.